The Impact of Hospitality Work Environment on Employees’ Turnover Intentions During COVID-19 Pandemic: The Mediating Role of Work-Family Conflict - Abdou, Ahmed Hassan; Khalil, Ayman Ahmed Farag; Mahmoud, Hassan Marzok Elsayed; Elsaied, Mohamed Ahmed; Elsaed, Ahmed Anwar (Frontiers in Psychology, 2022)
Employees’ turnover intentions and work-family conflict as a result of the hospitality work environment are considered the major global challenges confronted by hospitality organizations, especially in the era of COVID-19. This study aims at identifying the impact of the hospitality work environment on WFC as well as turnover intentions and examining the potential mediating role of WFC in the relationship between work environment and turnover intentions, during the COVID-19 pandemic in a sample of three- and four-star resorts in Egypt. A total of 413 resorts employees from Egyptian destinations (Sharm El-Sheikh and Hurghada) participated in the study. The findings of the Structural Equation Modeling (SEM) revealed that the hospitality work environment significantly and positively affects employees’ turnover intentions and work-family conflict. In the context of the mediating role of work-family conflict, results illustrated that WFC significantly partially mediates the relationship between the hospitality work environment and turnover intentions. Upon these findings, the study suggests that to prevent WFC and eliminate turnover intentions among resorts’ employees, an urgent need to create a better work environment is vitally important. limitations and future research directions have been discussed.